Efektivitas Implementasi Teknologi Informasi pada Bimbingan & Konseling di Era Pandemi - Muhammad Fauzan; Nurhuda Maulana Sidiq; Hafsah Nugraha (Jurnal Pembelajaran Inovatif, 2021)
The phenomenon of distance learning (PJJ) during the Covid-19 pandemic led to various problems in education. One of them is the application of PJJ where the learning emphasizes the cognitive aspects, and the learning is designed how students must develop by learning cognitive, but the affective and psychomotor aspects are not given attention. Especially affective, where parents who are responsible for learning their children at home, not all of them have the competence to teach their children about attitudes, good behavior, or knowledge about mental health and mental health. counseling which must exist in this case, cannot perform services directly so it requires the application of information technology in it. This study aims to (1) determine the level of effectiveness in the use of information technology for counseling, (2) describe the various ways and tools in information technology that can be implemented to assist counseling services. In the procedure for compiling this journal, the method used to compile it is literature study. This technique is carried out by collecting various data from various literature that is relevant and guaranteed to the problems and research discussed in the journals. This journal describes the problem of the effectiveness of IT implementation at counseling in a descriptive and hierarchical manner regarding various studies conducted in literature data which is the source of reference. The research method used is a literature study by examining various literature that is relevant to the title raised by the author. The results of this study are a description of the results of processing data from various reference literatures regarding the effectiveness of IT implementation in BK in the Pandemic Era with Distance Learning (PJJ).